Proibida a entrada de pessoas não autorizadas: um estudo sobre as guerrilhas artísticas urbanas - Cerullo, Adriano Ribeiro (2016)
This research seeks to nominate an artistic and cultural phenomenon present in contemporary history. Its evidences are perceived through academic papers, visual demonstrations, photographic registries, testimonials from artists and above all, as a result of the profound transformations in the contemporary art scene, resulting from the post-war environment. The "Guerrilla Art" denomination arises in the 1960s, parallel to the flourishing of the counterculture movement - but it is not presented, however, as a settled definition to a general tendency or an artistic movement. It trespasses the system, sneaking out of dogmas and bibliographical manifestos – as well as the guerrilla warriors violate the enemy territory, weakening their oppressive structures from the inside out. First of all, the work aspirations are the following: the identification of the artistic guerrilla concepts; the dialogue between the related authors; and the comprehension of the constitutive elements - the art, the city and the contemporaneity. Secondly, the investigation seeks to identify a historical/contextual vector to guide through a chronological evolution, emphasising on the study of the cultural operators from the 1960s; from this point, the events, characters and episodes are explored, under the purpose of revealing a trend track. Finally, on the third step, based on this stored conceptual repertoire, the researcher indicates samples of contemporary artists’ works, considered revolutionary ones, and he analyses them for identifying a possible artistic guerrilla methodology. Thus, on the behalf of this knowledge, the work intends to demonstrate the existence of a creative-reactive artistic behaviour.